Manipulating exudate composition from root apices shapes the microbiome throughout the root system. Issue 4 (22nd July 2021) - Kawasaki, Akitomo; Dennis, Paul G; Forstner, Christian; Raghavendra, Anil K H; Mathesius, Ulrike; Richardson, Alan E; Delhaize, Emmanuel; Gilliham, Matthew; Watt, Michelle; Ryan, Peter R
Abstract: Certain soil microorganisms can improve plant growth, and practices that encourage their proliferation around the roots can boost production and reduce reliance on agrochemicals. The beneficial effects of the microbial inoculants currently used in agriculture are inconsistent or short-lived because their persistence in soil and on roots is often poor. A complementary approach could use root exudates to recruit beneficial microbes directly from the soil and encourage inoculant proliferation. However, it is unclear whether the release of common organic metabolites can alter the root microbiome in a consistent manner and if so, how those changes vary throughout the whole root system. In this study, we altered the expression of transporters from the ALUMINUM-ACTIVATED MALATE TRANSPORTER and the MULTIDRUG AND TOXIC COMPOUND EXTRUSION families in rice ( Oryza sativa L.) and wheat ( Triticum aestivum L.) and tested how the subsequent release of their substrates (simple organic anions, including malate, citrate, and γ-amino butyric acid) from root apices affected the root microbiomes. We demonstrate that these exudate compounds, separately and in combination, significantly altered microbiome composition throughout the root system. However, the root type (seminal or nodal), position along the roots (apex or base), and soil type had a greater influence on microbiome structure than the exudates. These results reveal that the root microbiomes of important cereal species can be manipulated by altering the composition of root exudates, and support ongoing attempts to improve plant production by manipulating the root microbiome. Abstract : One-sentence summary: The root microbiome of rice and wheat can be manipulated by altering the activity of root transporters and exudates.